THE EFFECT OF BANK SOUNDNESS LEVEL AND MACROECONOMIC FACTORS ON THE STOCK PRICE OF PT BANK RAYA INDONESIA Tbk (AGRO) DURING THE POST-COVID-19 PANDEMIC RECOVERY PERIOD (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of bank soundness level, as proxied by the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR), as well as macroeconomic factors including inflation, the BI 7-Day Reverse Repo Rate, and the IDR/USD exchange rate, on the stock price of PT Bank Raya Indonesia Tbk (AGRO) during the post-COVID-19 pandemic recovery period of 2020–2023. The study uses a quantitative approach with the multiple linear regression analysis method. The data used are secondary data in the form of the company's quarterly financial statements and macroeconomic data published by Bank Indonesia during the research period, yielding 16 observations. Before hypothesis testing was conducted, the data were first tested using classical assumption tests to ensure the regression model met the Best Linear Unbiased Estimator (BLUE) criteria. The results show that simultaneously, all independent variables have a significant effect on the stock price of PT Bank Raya Indonesia Tbk (AGRO). Partially, only the inflation and BI 7-Day Reverse Repo Rate variables have a significant effect on the stock price, while CAR, NPL, NIM, BOPO, LDR, and the IDR/USD exchange rate do not show a significant effect. The coefficient of determination (R²) value of 0.904 indicates that 90.4% of the variation in stock price can be explained by the variables in the model, while the remaining 9.6% is influenced by other factors outside the study. These findings imply that macroeconomic conditions play a more dominant role than bank soundness indicators in influencing AGRO's stock price during the post-pandemic economic recovery period.